2020
DOI: 10.1093/mnras/staa245
|View full text |Cite
|
Sign up to set email alerts
|

Reverse engineering the Milky Way

Abstract: The ages, metallicities, alpha-elements and integrals of motion of globular clusters (GCs) accreted by the Milky Way from disrupted satellites remain largely unchanged over time. Here we have used these conserved properties in combination to assign 76 GCs to 5 progenitor satellite galaxies -one of which we dub the Koala dwarf galaxy. We fit a leaky-box chemical enrichment model to the age-metallicity distribution of GCs, deriving the effective yield and the formation epoch of each satellite. Based on scaling r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
103
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(118 citation statements)
references
References 53 publications
15
103
0
Order By: Relevance
“…Massari et al (2019) also found evidence for a population of GCs in the Milky Way at low energies (the L-E group) which do not appear to have formed in situ in the Galaxy (the GCs have ages and metallicities consistent with the 'accreted' or 'satellite' branch 1 ), and are not connected to previously known merger events. This GC population is plausibly consistent with the proposed Kraken (Kruijssen et al 2019b) accretion event, which was predicted based on number of GCs in the 'satellite' branch of the Milky Way GC age-metallicity distribution (see also Forbes 2020;Kruijssen et al 2020).…”
Section: Introductionsupporting
confidence: 84%
“…Massari et al (2019) also found evidence for a population of GCs in the Milky Way at low energies (the L-E group) which do not appear to have formed in situ in the Galaxy (the GCs have ages and metallicities consistent with the 'accreted' or 'satellite' branch 1 ), and are not connected to previously known merger events. This GC population is plausibly consistent with the proposed Kraken (Kruijssen et al 2019b) accretion event, which was predicted based on number of GCs in the 'satellite' branch of the Milky Way GC age-metallicity distribution (see also Forbes 2020;Kruijssen et al 2020).…”
Section: Introductionsupporting
confidence: 84%
“…Myeong et al (2019) suggest it is associated with the Sequoia accretion event based on the actions, inclination and eccentricity of its orbit, while MKH19 suggest it is associated with G-E/S based on the binding energy of its orbit within the MW. Similarly, Forbes (2020) assigned Cen and NGC 1851 as the NSCs of Sequoia and G-E/S, respectively.…”
Section: Ngc 5139 ( Cen)mentioning
confidence: 99%
“…MKH19 unambiguously assign NGC 6273 to the 'low energy' group of GCs. This group has subsequently been associated with the Kraken merger event (Kruijssen et al 2019b(Kruijssen et al , 2020Pfeffer et al 2020;Forbes 2020). Recently, Horta et al (in preparation) have reported the discovery of the stellar component of Kraken, based on a combination of abundances and kinematics, lending further support to the existence of this relatively massive accreted galaxy.…”
Section: Ngc 6273 (M19)mentioning
confidence: 99%
See 1 more Smart Citation
“…Marín-Franch et al 2009;Forbes & Bridges 2010;Leaman, VandenBerg & Mendel 2013). This shallower branch has been demonstrated to be made up of accreted clusters (Kruijssen et al 2019b;Massari, Koppelman & Helmi 2019;Forbes 2020), and it also appears as a separate branch for metal-poor GCs in the α-Fe plane (e.g. Horta et al 2020c).…”
mentioning
confidence: 91%